2017
DOI: 10.1088/1741-4326/aa827a
|View full text |Cite
|
Sign up to set email alerts
|

New evidence and impact of electron transport non-linearities based on new perturbative inter-modulation analysis

Abstract: Abstract.A new methodology to analyze non-linear components in perturbative transport experiments is introduced. The methodology has been experimentally validated in the Large Helical Device (LHD) for the electron heat transport channel. Electron cyclotron resonance heating (ECRH) with different modulation frequencies by two gyrotrons have been used to directly quantify the amplitude the non-linear component at the inter-modulation frequencies. The measurements show significant quadratic non-linear contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…This test has also been experimentally applied and can be found in Ref. 21. There, it is shown that indeed if the perturbation is chosen relatively small even for a small perturbation, one can observe non-linear components.…”
Section: Fig 11mentioning
confidence: 95%
See 1 more Smart Citation
“…This test has also been experimentally applied and can be found in Ref. 21. There, it is shown that indeed if the perturbation is chosen relatively small even for a small perturbation, one can observe non-linear components.…”
Section: Fig 11mentioning
confidence: 95%
“…This can be done using natural interaction between sawtooth and modulated electron cyclotron heating (ECH) 19 or using directly two modulated ECH sources. 20,21 Analyzing higher harmonics can specifically be used to test the linearity of the experiment, which is a necessary condition when compared to linearized physics models.…”
Section: Physical Restrictions On the Modulation Frequencymentioning
confidence: 99%
“…The calculated standard deviations are very similar (note the logarithmic scale). Only at low-frequency there is some deviation due to the transient, which could be further improved using the LPM-method introduced in [20,21]. Methods number (II) or (III) are used to calculate the variance, i.e., the SNRs, of the individual harmonic components.…”
Section: Three Different Ways To Estimate the Stochastic Uncertaintymentioning
confidence: 99%
“…Then, the variance of the integral based on propagation of uncertainty and averaging of noise (factor 2) is calculated as follows t) . (20) Given that at small ρ only a few samples are available, it is important to remember that there is an additional error on the estimate based on the formula for the trapezoidal approximation, i.e.,…”
Section: Variance Calculation On Heat Fluxmentioning
confidence: 99%
See 1 more Smart Citation